Bioremediasi Limbah Cair Industri Tahu Menggunakan Larutan EM4 secara Anaerob-Aerob - Deffy, Trisca; Nilandita, Widya; Munfarida, Ida (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2020)
This research using a bioremediation treatment process with anaerobic-aerobic system by mixing tofu liquid waste and EM4 solution into the reactor. The variation of EM4 solution that will be used in this research is 1/20 of concentration with 1/10 of concentration and detention time. This research was conducted for 8 days. The result showed that EM4 solution was able to reduce BOD, COD, and TSS by usinng variations in concentration and detention time. The most significant decrease in BOD, COD, adn TSS levels occured on the 8 day. BOD levels for the first reactor at a concentration of 1/10 with a removal efficiency of 48,98% and a second reactor withÂ  removal efficiency of 48,98%. For the 1/20 concentration the removal efficiency was 37,33% and in second reactor the removal efficiency was 37,34%. COD levels for the first reactor at a concentration of 1/10 with a removal efficiency of 61,82% and a second reacotor with removal efficiency of 62,10%. For the 1/20 concentration the removal efficiency was 30,39% an in second reactor the removal efficiency was 34,98%. TSS levels for the first reactor at a concentration 1/20 with removal efficiency of 41,17% and in the second reactor the removal efficiency of 43,59%. At 1/20 concentration the removal efficiency of TSS levels was 1,02% in the first reactor and in the second reactor the removal efficiancy was 5,10%. Bioremediation using EM4 solution can be used to reduce levels of BOD, COD, and TSS of tofu liquid waste according to the applicable quality standards